2018
DOI: 10.1177/1044207318771673
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Career and Technical Education on Students With Disabilities

Abstract: Evidence suggests that participating in career and technical education (CTE) in high school, on average, positively affects general education students when transitioning from education to the workforce. Yet, almost no large-scale causal research has explored whether academic benefits also accrue to students with disabilities in CTE. This omission is glaring given that students with disabilities participate in high school CTE programs at high rates. We use multiple years of administrative data from Massachusett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…As discussed above, that trend is consistent with the hypothesis that federal policies from the early 2000s placed an increased emphasis on academic coursework over occupational CTE coursework. Recent evidence has linked concentrated CTE participation to improved graduation and employment for students with disabilities (Dougherty et al, 2018; Lee et al, 2016; Theobald et al, 2019; Wagner et al, 2016), so while this earlier research is not causal in nature, the declining participation in CTE by students with disabilities documented in this study could be interpreted negatively for policymakers and educators who want to improve outcomes for students with disabilities (e.g., Lipscomb et al, 2017). On the other hand, our alternative coding approach suggests that the decline in CTE participation is driven by movement out of courses that are no longer considered CTE and are not included in the definition of CTE in these more recent studies, so further research is necessary to disentangle the impacts of the these two trends on student outcomes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As discussed above, that trend is consistent with the hypothesis that federal policies from the early 2000s placed an increased emphasis on academic coursework over occupational CTE coursework. Recent evidence has linked concentrated CTE participation to improved graduation and employment for students with disabilities (Dougherty et al, 2018; Lee et al, 2016; Theobald et al, 2019; Wagner et al, 2016), so while this earlier research is not causal in nature, the declining participation in CTE by students with disabilities documented in this study could be interpreted negatively for policymakers and educators who want to improve outcomes for students with disabilities (e.g., Lipscomb et al, 2017). On the other hand, our alternative coding approach suggests that the decline in CTE participation is driven by movement out of courses that are no longer considered CTE and are not included in the definition of CTE in these more recent studies, so further research is necessary to disentangle the impacts of the these two trends on student outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…For instance, students with disabilities who take more CTE courses in high school are more likely to graduate and be employed within 2 years of graduation compared with similar students with disabilities who take fewer CTE courses. These links persist even after controlling for baseline (i.e., demographic and academic) differences between students who do and do not participate in CTE (e.g., Dougherty et al, 2018; Lee et al, 2016; Theobald et al, 2019; Wagner et al, 2016).…”
mentioning
confidence: 94%
“…To study the education and work outcomes of students in secondary and postsecondary CTE programs in Florida, Jacobson and Mokher (2014) utilized education and employment records to follow a cohort of ninth‐grade students for 10 years, finding that high school CTE had little effect on education outcomes such as graduation and continuing to college when controlling for background and family variables; they did find some significant differences between urban and rural students in CTE concentration and continuation to college, though the college outcome was attributable to differences in high school performance and family income. In two quasi‐experimental studies using statewide linked data sets, Dougherty et al (2018) investigated the impact of regional vocational and technical schools in Massachusetts, which were argued to demonstrate higher quality in terms of comprehensiveness of curriculum and instruction. Controlling for selection bias for high school attendees of CTE programs, he found that attending a regional vocational and technical school increased likelihood of graduation by 32% (though it did not affect standardized math and reading scores).…”
Section: The Ets Research Framework For Cte: An Inclusive Model For a Complex Systemmentioning
confidence: 99%
“…Although CTE is critically important in meeting workforce development and skill demands of jobs in the 21st century, participation of students with disabilities in secondary CTE in the professional literature often remains elusive (Casale-Giannola, 2012). Reports find a higher concentration of students with disabilities participating in CTE (Dougherty et al, 2018; Gray & Lewis, 2018). However, participation varies across states and regions.…”
Section: The Promise Of Cte To Facilitate Secondary Special Educationmentioning
confidence: 99%
“…Among these predictors of post-school success is secondary career and technical education (Career Technical Education [CTE]; Harvey, 2002). Although research has indicated that participation of students with disabilities in secondary CTE increases the likelihood of positive outcomes after high school, access to secondary CTE programs for students with disabilities remains limited (Dougherty, Grindal, & Hehir, 2018). In addition, research focused on students with disabilities and participation in CTE is not prevalent in special education, secondary transition, or CTE literature.…”
mentioning
confidence: 99%